Newborn Screening for Lysosomal Disease: Mission Creep and a Taste of Things to Come? - Bridget Wilcken (International Journal of Neonatal Screening, 2018)
Newborn screening for several lysosomal disorders can now be accomplished successfully for case finding. However, many cases identified do not require immediate intervention and it is not yet clear, for some disorders, if there is a benefit in early diagnosis for those cases, or what should be called a benefit. Diagnosing adult-onset cases, especially when there are quite imperfect genotype-phenotype correlations, represents a significant expansion of what has heretofore been considered the aim of newborn screening. This mission creep should be carefully discussed, and certain aspects of newborn screening strengthened. We should all proceed with caution in this field.